Sustainability and repeatability of postactivation potentiation - McLaren, T.; King, D. L.; Sforzo, G. A. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: This study investigated the duration and repeatability of postactivation potentiation (PAP) benefits within a single exercise session. Specifically examined were the recurring effects, over multiple sets, of heavy back squats on repeated sprint times.